2018
DOI: 10.1063/1.5034243
|View full text |Cite
|
Sign up to set email alerts
|

On the transverse dielectric permittivity of the collisionless plasmas with quantum effects

Abstract: An expression is found for the transverse dielectric permittivity of a collisionless nonrelativistic fully ionized plasma, which consequently takes into account quantum effects in the presence of an intrinsic magnetic moment of plasma particles. The frequency and spatial dispersion of the dielectric permittivity under various thermodynamic parameters are investigated. The obtained dielectric permittivity is compared with the known theoretical results for a collisionless plasma in the classical limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…According to [12], the full SEDER in plasma medium E(ω), which includes the zero fluctuations in plasma is the sum of two terms Here ( ) e w k, tr is the transverse dielectric permittivity (TDP) of non-relativistic plasma, which takes into account spatial and frequency dependence of electromagnetic field as well as arbitrary strong interaction between charged particles in the system. However, the TDP for strongly interacted plasma is unknown and we use for further calculations the most accurate form of TDP for the case of a weak Coulomb interaction between charged particles in quasiclassial and quasineutral plasma medium [13].…”
Section: General Formulae For the Seder In Electron Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [12], the full SEDER in plasma medium E(ω), which includes the zero fluctuations in plasma is the sum of two terms Here ( ) e w k, tr is the transverse dielectric permittivity (TDP) of non-relativistic plasma, which takes into account spatial and frequency dependence of electromagnetic field as well as arbitrary strong interaction between charged particles in the system. However, the TDP for strongly interacted plasma is unknown and we use for further calculations the most accurate form of TDP for the case of a weak Coulomb interaction between charged particles in quasiclassial and quasineutral plasma medium [13].…”
Section: General Formulae For the Seder In Electron Gasmentioning
confidence: 99%
“…In this work, using the results of analytical and numerical calculations [13] for TDP of almost ideal plasma, we consider the influence of non-ideality on low frequency behavior of the full SEDER (1) when the parameter, characterized the plasma non-ideality (or Coulomb interaction parameter) Γ=e 2 n 1/3 /T increases. The concrete form of the TDP ( ) e w k, tr which we use for weakly non-ideal and non-relativistic electron gas is determined by the relations where h = L n e e e 3 , W=ÿω/T, 12 is the thermal de Broglie wavelength for electrons and 1 F 1 (α,β,z) is the degenerate hypergeometric function.…”
Section: General Formulae For the Seder In Electron Gasmentioning
confidence: 99%
“…Influence of the spin effects on the dielectric permeability of plasmas at the arbitrary temperatures is considered in Ref. [31]. It is found that the plasma can demonstrate the paramagnetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Более того, даже для идеального электронного газа имеется только интегральное представление при произвольном вырождении электронов (см. подробнее [17]).…”
unclassified